(untitled) (Journal of the College of Education for Women, 2025)
The study aimed to examine compulsive shopping disorder (oniomania) and its relationship with self-esteem among employees in the city of Hebron, both male and female. To achieve this, the researchers used a questionnaire as the study method to collect data. The study used the self-esteem scale developed by Rashmawi (2013) and the compulsive shopping disorder scale as defined by Moon (2019). After identifying 152 employees who met the criteria for compulsive shopping disorder from all employees for the year 2023, they were selected randomly. According to the results of the study, the motives for shopping among the sample ranged from compulsive (impulsive) to recreational. The results also showed that, from their perspective, employees with compulsive shopping disorder in Hebron had modest self-esteem. Moreover, the study found a statistically significant negative correlation between self-esteem levels among employees in Hebron and compulsive shopping disorder. The results also indicated a relationship between compulsive shopping disorder and self-esteem among employees in the city of Hebron, with self-esteem affecting compulsive shopping disorder. Based on these results, the study provided a set of recommendations, the most important of which were: increasing awareness about shopping behavior and planning for it, through holding seminars and training courses for employees, in light of the significant degree of compulsive shopping disorder observed among the respondents.